Magnetism and Magnetic Materials (IntechOpen, 2023)
The aim of the book is to provide the reader with a comprehensive overview of the current research in the interesting field of magnetism and magnetic materials. Some very interesting topics like erasing and retrieving the particular magnetic domain of a ferromagnetic thin film, the single domain behaviour of magnetic nanowire with dimension less than 100 nm, magneto-transport behaviour of Heusler alloys etc. have been covered.